Commodity risk assessment of Alnus cordata, Alnus glutinosa and Alnus incana plants from the UK - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Paolo Gonthier; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘high‐risk plants, plant products and other objects’. Taking into account the available scientific information, including the technical information provided by the applicant country, this Scientific Opinion covers the plant health risks posed by the following commodities: Alnus cordata, A. glutinosa and A. incana graftwood, bare‐root plants and rooted plants in pots up to 7 years old imported into the EU from the UK. A list of pests potentially associated with the commodities was compiled. The relevance of each pest was assessed based on evidence following defined criteria. Two EU‐quarantine pests (Entoleuca mammata, Phytophthora ramorum (non‐EU isolates)) and one non‐quarantine pest (Phytophthora siskiyouensis) were selected for further evaluation. For the selected pests, the risk mitigation measures implemented in the UK and specified in the technical dossier were evaluated taking into account the factors reducing their efficacy. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies between the pests evaluated, with E. mammata being the pest most frequently expected on imported Alnus spp. small trees. Expert knowledge elicitation indicated, with 95% certainty, that between 9927 and 10,000 per 10,000 Alnus spp. small trees (bare‐root plants or rooted plants in pots up to 7 years old) would be free from E. mammata.